Growth and Survival Rate of Pocillopora spp. Fragments on Coral Tree and Coral Table Media in Semut Kecil Island, Anambas Islands - Ariqa Iriani, Fringgar; Arifin , Reyhan; Jerry Winata, Marcellinus; Rifat Muharam , Muhammad; Permata Putri , Novita; Dewi Ruswanti, Corina; Rahman Ritonga, Abdul; Riviani , Riviani; Riyanti (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research Pocillopora spp. grew faster on coral tree media (0.55 cm/month) than on coral table media (0.15 cm/month). Survival rates were high, with 97.3% on coral trees and 87.0% on coral tables, proving both methods effective. Coral growth on table media was slower due to sediment accumulation, while tree media provided more stable growth. ANOVA analysis showed no significant effect of transplant media on growth and survival, confirming adaptability. Both methods are viable for large-scale coral reef restoration, especially in the Anambas Islands and similar ecosystems. Abstract Pulau Semut Kecil, Anambas Islands, are located within the coral reef triangle, as one of the largest Marine Protected Areas (MPAs) in Indonesia. Coral reefs possess significant functional attributes within ecosystems, and their condition is progressively deteriorating due to anthropogenic activities. This situation necessitates restoration endeavors, primarily through coral transplantation methodologies. The methods involved the introduction or relocation of donor corals into substrates such as tree transplantation media and tables, exhibiting high success rates. This study was conducted to determine the growth and survival rate of Pocillopora spp. The direct survey approach was used and the different coral transplanting media were statistically analyzed with the ANOVA test and SPSS software. The results of the growth of coral fragments Pocillopora spp. Reported coral tree media and table with an average value of 0.55 cm/month and 0.15 cm/month. The survival rate of Pocillopora spp. coral fragments in tree media and table was 97.3% and 87.0%. The media for dropping coral trees and table did not affect the growth and survival rate. This coral transplantation method can facilitate for the restoration of degraded ecosystem and ecological succession.